EMPOWERING WOMEN FARMERS THROUGH AGRICULTURAL EXTENSION APPROACH FOCUSING ON GENDER EQUALITY AND SUSTAINABILITY - Eko Binti Lestari; Rawuh Yuda Yuwana (Acceleration: Multidisciplinary Research Journal, 2023)
This research explores the transformative potential of gender-focused agricultural extension programs in empowering female farmers and advancing sustainable agricultural practices. The study employs a mixed-methods approach, drawing insights from existing literature and combining quantitative and qualitative analyses to uncover the multifaceted impact of these interventions. The findings underscore a notable enhancement in women's agency and participation, underlining the importance of promoting gender equality within the agricultural sector. Empowered female farmers exhibit a proclivity towards sustainable farming practices, contributing to environmental sustainability through the adoption of eco-friendly techniques. Economic empowerment emerges as a key outcome, as empowered women experience improved livelihoods and income, ultimately leading to poverty reduction and socio-economic development within their communities. The research findings have direct policy implications, highlighting the necessity of gender-sensitive policies, equitable resource allocation, and the removal of legal and policy barriers to ensure sustained empowerment. These comprehensive insights serve as a valuable resource for policymakers, practitioners, and researchers aiming to advance gender equality, environmental sustainability, and socio-economic development within the agricultural domain.